ChemInform Abstract: Homopetasinic Acid Isolated from Diaporthe sp. Strain 1308‐05. Issue 27 (16th June 2016) - Ito, Atsushi; Kumagai, Ikuya; Maruyama, Miku; Maeda, Hayato; Tonouchi, Akio; Nehira, Tatsuo; Kimura, Ken‐ichi; Hashimoto, Masaru
Abstract: isolation, structure determination and biological activities